Assessing Public Service Level: Evidence from Ngawi Regency In 2024 - Cahyadin, Malik; Mafruhah, Izza; Ismoyowati, Dewi; Hasana, Nurul; Istiqomah, Nurul (Efficient: Indonesian Journal of Development Economics, 2025)
Public service measurement constitutes a follow-up to the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017, serving as a metric for evaluating public performance and the governance thereof. The present study employs a multifaceted approach to assess the quality of public services in Ngawi Regency during the year 2024, utilising a combination of index and analytic hierarchy process methodologies. The respondent was set using purposive sampling method covers 500 individuals and 13 local apparatuses of Ngawi Regency. The findings reveal that the indexes of public service in public service malls at the regency and sub-district levels were 83.33 and 82.59 respectively. The priority factor values that constitute public service in sequence are as follows: reliability (0.206), tangibility (0.179), empathy (0.165), assurance (0.154), responsiveness (0.152), and general (0.144). Consequently, the Ngawi Regency Government can leverage online services to enhance public services and prioritise the factors contributing to the public service index.